BODY CONDITION SCORE IN DROMEDARY CAMEL : A TOOL FOR MANAGEMENT OF REPRODUCTION - Faye, B.; Bengoumi, M.; Cleradin, A.; Tabarani, A.; Chilliard, Y. (Emirates Journal of Food and Agriculture, 2017)
The ability of camels to cope with food shortage is the result of a long evolutionary process in natural conditions where food ability seasonally fluctuates. In arid conditions, all the adaptive mechanisms and especially body fat mobilisations strategies are of considerable importance in determining reproductive performance. In the camel, the hump is the most important fat storage place accessible to external observation. In a study performed in Moracco on 655 she-camels from different areas, data on body size (circumference and height of the hump, thigh circumference) and on perceptible fat status of different anatomical places( spinous and transverse process of vertebra perceptible or not, hollow of flank present or not, ischial tuberosity and coxal tuberosity proeminent or not, ribs visible or not) were collected. Data are treated with cluster analysis in order to identify the types of body conditons. The classes of body conditions can be associated to a specific score. The relationship between this score and fattening ability if the camel have to be deepened with adipocyte measurement. The body scoring appear as a better tool than the hump measurin. Finally, it seems that the body conditions score in camel is not mainly linked to the size of the hump.